Hubungan Tingkat Spiritualitas dengan Kualitas Hidup Pasien Gagal Ginjal Kronik selama Masa Pandemi Covid-19 - dewi adnan; Dewi Gayatri; Dhea Natashia; Wati Jumaiyah; Kustiyuwati Kustiyuwati (Jurnal Kesehatan Komunitas, 2022)
Patients with chronic kidney disease who undergo hemodialysis are very susceptible to COVID-19 infection. The level of spirituality has a very important role in alleviating suffering and also has an influence on health outcomes in order to maintain the quality of life of patients with CKD. This study aims to identify the relationship between Spirituality and Quality of Life of patients with CKD during the COVID-19 pandemic. This research method uses descriptive analytic with cross sectional approach. The sample of this study were 154 patients with Chronic Kidney Failure who were at the Islamic Hospital Jakarta Pondok Kopi. The measurement instrument uses a Spirituality Level scale that adapts the daily spiritual experience scale (DSES) and a quality of life scale that adapts kidney disease and quality of life (KDQOL-36TM). Data collection using google form is carried out for ± 1 month, data processing using SPSS version 25. Results Statistical test using binary logistic regression analysis found a significant relationship between spirituality level and quality of life (B: 1.513. p = 0.001, OR: 4.539, 95% CI: 1.880; 10.963). The conclusion is that the quality of life of patients with CKD during the COVID-19 pandemic can be maintained by increasing the patient's spirituality level after being controlled by social support, Hb value, length of illness and comorbidities. This study recommends the need for nurses to increase the level of spirituality in patients with chronic kidney failure in order to improve their quality of life.